Review Artikel: Formulasi Lipstik Dengan Menggunakan Bahan Alam Sebagai Pewarna Alami - Nia Yuniarsih; Amelia Putriana; Dyah Kharisma Ariyanti; Ina Nurunnisa; Muhammad Gilang; Sahrul Setiawan; Tasya Putri; Tia Laelasari (Journal of Pharmaceutical and Sciences, 2023)
Lipstick is a cosmetic product used to color lips, giving an artistic effect on the face that can enhance the aesthetics of facial make-up. Besides being able to provide attractive colors, this lipstick must also contain dyes that are safe to use. As a natural ingredient in making lipstick, various natural ingredients can be used in the form of extracts such as leaves, flowers, fruit and others. The method used in this study consisted of database searches through Pubmed, Science Direct and Google Scholar for various scientific articles published between 2013 and 2023. And the purpose of this study was to determine the composition of lipsticks that use natural ingredients as natural dyes. Literature search results that meet these criteria yield up to 20 references. Based on a review of various scientific literature, extracts from natural ingredients can act as natural dyes.